Impact of information technologies (IT) implementation on over\all TSC performance - Abdul Hamid, Abu Bakar (2012)
Tourism sector is known for its sophistication and interdependency where performance of one player would greatly influence the business operations of others in the sector. Hence, practices of supply chain management (SCM) have become a must for firms within this sector to coordinate their business operations. Despite the growing importance of SCM practices within tourism sector, only few empirical researches have been done in the area of tourism supply chains (TSC). Accordingly, this study attempts to empirically explore supply chain practices within Malaysian tourism firms with the focus on the impact of information technologies (IT) implementation towards overall TSC performance. About 331 questionnaires were electronically mailed to tour operators and agents where the response rate was about 36%. Findings indicate that IT implementation significantly influences the overall TSC performance where firms with advanced IT implementation level tend to enjoy a better growth in the overall TSC performance.